Icelandic Scribes: Results of a 2-Year Project - McDonald Werronen, Sheryl (Humanities Commons, 2018)
This paper introduces an online catalogue of an early modern library: the main digital output of the authors individual research project Icelandic Scribes (20162018 at the University of Copenhagen). The project has investigated the patronage of manuscripts by Icelander Magns Jnsson Vigur (16371702), his network of scribes and their working practices, and the significance of the library of handwritten books that he accumulated during his lifetime, in the region of Iceland called the Westfjords. The online catalogue is meant to be a digital resource that reunites this library virtually, gives detailed descriptions of the manuscripts, and highlights the collections rich store of texts and the individuals behind their creation. The present paper also explores some of the challenges of integrating new data produced by this and other small projects like it with existing online resources in the field of Old Norse-Icelandic studies. This project has received funding from the European Unions Horizon 2020 research and innovation programme under the Marie Skodowska-Curie grant agreement No. 654825.